Association of Gabapentin or Pregabalin Use and Incidence of Acute Angle-closure Glaucoma. Issue 9 (September 2019) - Browne, Mitchell J.; Zakrzewski, Helena; Carleton, Bruce; Etminan, Mahyar; Mikelberg, Frederick S.
Abstract : Precis: Gabapentin and its derivatives have numerous indications and are commonly prescribed medications. In this article, we provide evidence of a link between gabapentinoid use and incidence of acute angle-closure glaucoma. Purpose: Gabapentinoids, such as gabapentin and pregabalin, are commonly prescribed classes of drugs in North America. We sought to determine the association of gabapentin or pregabalin use and the incidence of acute angle-closure glaucoma. Materials and Methods: This was a nested case-control study. All adult patients who developed acute angle-closure glaucoma between January 1, 2006 and December 31, 2016, and enrolled in the PharMetrics Plus database were eligible for inclusion. A conditional logistic regression model was constructed to assess the association between gabapentin or pregabalin use and the incidence of acute angle-closure glaucoma. Results: Incidence of acute angle-closure glaucoma was found to be statistically significantly associated with the use of gabapentin in the year before diagnosis [relative risk (RR), 1.42; 95% confidence interval (CI), 1.00-2.00]. This association was not observed to be statistically significant with the current use of gabapentin (RR, 1.28; 95% CI, 0.77-2.12). Incidence of acute angle-closure glaucoma (AAG) was not found to be statistically significantly associated with either use of pregabalin in the year before diagnosis or current use (RR, 1.00; 95% CI, 0.51-1.93 and RR, 1.50; 95% CI, 0.66-3.38, respectively). Conclusions: To the best of our knowledge this is the first study to investigate the association between gabapentin or pregabalin use and the incidence of AAG. Gabapentin use in the year before diagnosis was found to be associated with the incidence of AAG. Abstract : Supplemental Digital Content is available in the text.